Moralistul Creangă - Eugen Simion (Revista de Istorie și Teorie Literară)
The hypothesis of the present article is that Ion Creangă, one of the great Romanian prose writers (1837–1889), is a moralist who likes to observe the human nature and to judge it. The author presents the state of critical reviews of Ion Creangă as a moralist and points to the originality of his approach. A historical overview of the moralists in the Romanian literature is giving the clear picture of the place occupied by Ion Creangă. The arguments used to prove this hypothesis, refer to Creangă’s techniques as an ethical / moral judge: the use of various folk sayings and the illustration of the traditional / folk patterns of thinking. The study sheds clear and new perspectives on Creangă’s artistry and the philosophic vision concerning life.